2021
DOI: 10.1021/acsaem.1c02291
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Enhanced Charge Separation and Transfer in Cocatalyst-Free Hematite Photoanode by Mo/Sn Codoping

Abstract: It is well-known that sluggish surface charge transfer on a cocatalyst-free hematite photoanode limits its solar conversion efficiency in photoelectrochemical (PEC) water splitting. Here, Mo is used as a codopant synergistically with Sn in α-Fe2O3 to solve this problem. Besides causing a slight narrowing of bandgap, morphological change, and even sublimation loss of α-Fe2O3, Mo doping also imports low-valent Fe due to charge compensation with MoV/VI as indicated by X-ray photoelectron spectroscopy and Bader ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…3b and c . Subsequently, the 6% Mo-doped Fe 3 O 4 sample exhibited a completely different morphology, where the nanorods disappeared and an excess of surface floccules of Mo emerged on the surface of the nanoparticles, 47 as presented in Fig. 3d .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…3b and c . Subsequently, the 6% Mo-doped Fe 3 O 4 sample exhibited a completely different morphology, where the nanorods disappeared and an excess of surface floccules of Mo emerged on the surface of the nanoparticles, 47 as presented in Fig. 3d .…”
Section: Resultsmentioning
confidence: 95%
“…Upon doping, slight peak shis with a signicant decrease in peak intensity were manifested due to the enhanced structural disorder and amorphous nature of the high concentration of occules on the Mo-doped samples. 47 The crystallite size (D) of the prepared materials was measured using the Debye-Scherrer equation. The difference in crystalline size basically depends on the angles of diffraction and the effect of peak broadening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A photocurrent density of 1.97 mA cm −2 at 1.23 V RHE and a relatively low onset potential of 0.68 V RHE were obtained by a simultaneous introduction of Sn and Mo in α-Fe 2 O 3 , where the former accelerated charge separation by improving conductivity and the latter induced high density of surface trapping states, leading to the inhibition of charge recombination kinetics in surface states. 5 A significant increase in the concentration of (co)doped ions decreases the efficiency. By applying a computational method, Smart et al 6 recently found a doping clustering, which traps free-electron polarons and severely lowers the carrier concentration with respect to the doping concentration, to be responsible for the doping bottleneck in α-Fe 2 O 3 , and proposed a codoping with dopants having low binding energies for clustering, such as Sn–Ti, as a solution.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has received extensive attention for the direct utilization of solar energy to deal with environmental and energy problems. As one of the most important photocatalysts, hematite (Fe 2 O 3 ) has attracted much attention because of its low cost, suitable band gap (absorption of visible light), and thermodynamic stability. However, its photocatalytic efficiency is still limited by some shortcomings such as short-holes diffusion length, fast photoelectron pair recombination, and poor electron conductivity. , Currently, many strategies, including elemental doping, heterojunction formation, and defect engineering, have been used to modulate the properties of Fe 2 O 3 so as to improve the separation of photoelectron–hole pairs and finally achieve enhanced photocatalytic activity. …”
Section: Introductionmentioning
confidence: 99%